Analisis Kemampuan Komunikasi Siswa dalam Ekstrakurikuler Drumband di Sekolah Dasar - Nisrina Sofiliandini Sakinah; Irna Khaleda Nurmeta; Luthfi Hamdani Maula (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to analyze the development of students' communication skills through extracurricular drumband activities in elementary schools. This research focuses on the school where the research is conducted, namely SDN Pakujajar CBM, Sukabumi city. With a focus on the research indicators of respect, empathy, and audible, this research uses descriptive qualitative methods to collect data through observation, interviews and documentation. The results show an increase in students' communication skills, with respect for the individual's role in the group, support between fellow members, and the ability to convey messages clearly. Apart from improving musical skills. Supporting factors such as the role of trainers, school support, student participation, and parental attention are the keys to the successful implementation of this activity. Therefore, this research suggests that drumband extracurricular activities have a positive impact on musical skills, and effectively shape students' communication skills, which are useful for success in various aspects of life.